Segmental Model for Comparing the Value of Organizations (Utility-based) - D. N. Belykh (Финансы: теория и практика)
This paper presents a model for visualizing the organization’s activities based on the market value-to-sales ratio (utility coefficient), which is a segmented two-dimensional diagram (utility diagram). The aim of the study is to develop measures to improve the quality and effectiveness of management decisions taken to implement the principles of sustainable growth of a company’s capital value, considering the specifics of the business, with the identification of the optimal ratio of the structure of the balance of assets, costs and net profit with revenue, in order to find a compromise between the current value and development. The author used the following methods: financial ratios, statistical, balance, systematic and logical thinking, visual presentation. The results of the multivariate analysis indicate that there is a significant correlation between the utility and various ratios of financial reporting indicators for a representative sample of two hundred domestic and foreign companies. The article offers a model to assess the activities of organizations, including those not listed on the stock exchange, and correlate them using a matrix of key factors, according to their influence on the final cost of the business. The author concluded that the increase in the market value-to-sales ratio mainly depends on the profits of the asset, however, for different segments of the utility diagram, the influence of this factor is not the same. Effective strategies must be considered depending on the type of activity, then the productivity of solutions and their value for the market as a whole will increase significantly. The implementation of the model makes it possible to compare the dynamics of the activities of organizations with industry competitors for a selected period of time, at the strategic level to determine directions for increasing the utility coefficient, and in the future, it can be used as an alternative method for assessing the value of companies.